Tuning Catalytic Performance of C2N/GaN Heterostructure for Hydrogen Evolution Reaction by Doping. Issue 4 (12th February 2023) - Han, Shuang; Yang, Jian; Wei, Xiumei; Huang, Yuhong; Zhang, Jianmin; Wang, Zhenduo
Abstract: In this work, a systematic theoretical study of the hydrogen evolution reaction (HER) catalytic activity of C2 N/GaN heterostructure is carried out based on first principles. An indirect bandgap of 1.99 eV and type‐II band alignment are formed in the C2 N/GaN heterostructure, which can facilitate the spatially efficient separation of photogenerated carrier pairs, and the band edge position matches the reduction potential of water. The catalytic performance of the HER reaction at the C and N sites is compared and that the N site is better in performance is found, but still requires a potential barrier of 0.60 eV. In order to improve the catalytic performance of the C2 N/GaN heterostructure, an N atom is replaced by a P atom to obtain P‐C2 N/GaN. The band alignment of the P‐C2 N/GaN heterostructure is still type‐II, and the band edges satisfy the reduction potential of water. Fortunately, the P or N sites play a crucial role in the HER process with a relatively low overpotential of 0.38 eV, which suggests that P‐C2 N/GaN can improve the catalytic performance of the heterojunction. Overall, the P‐C2 N/GaN heterostructure has suitable band gap values and band edges, and efficient charge separation in the heterostructure makes it a promising HER catalyst. Abstract : The HER performances of pure C2 N/GaN and P‐doped C2 N/GaN heterostructure are systemically solved by the first‐principles calculations. The results demonstrate that the HER catalytic activity of P‐doped C2 N/GaN heterostructure has better HER performance than the pure C2 N/GaN heterostructure and P‐doping can effectively adjust the HER performance.